ISLAMIC PREACHING RHETORIC OF USTAZ ADI HIDAYAT’S (UAH) AND ITS SIGNIFICANCE AS SPEAKING MATERIALS FOR THE SECOND-YEAR SENIOR HIGH SCHOOL STUDENTS (RETORIKA DAKWAH USTAZ ADI HIDAYAT DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR TEKS CERAMAH KELAS XI SMA) - Hermandra Hermandra; Umi Kulsum; Elvi Citraresmana (Metalingua: Jurnal Penelitian Bahasa, 2022)
The objective of this study is to describe a preacher of Islam, Ustaz Adi Hidayat’s (UAH) preaching rhetoric. This study focuses on the structure, methods, and strategies used by UAH to convey Islamic messages. In addition, it emphasizes on the significance of research findings as speaking teaching materials for the second-year students of senior high schools. The preaching rhetoric used by the preacher was described by using the analysis method based on the rhetoric theory of preaching. The structure of the opening section or introduction to UAH’s preaching consisted of opening greetings, praises to Allah, greetings to the Prophet Muhammad, and an introductory statement to the subject of the preaching. The main body section of his preaching consisted of elaborations of arguments referring to the Quran and Hadith cited in fluent Arabic. The closing section or the conclusion section consisted of conclusions of the preaching materials, messages to remember Allah, Islamic stories in accordance with the messages and, closing greetings. The preaching method used by UAH was Al-Mauizah Al-Hasanah. The method contained persuasive statements, elaboration, appeals, and piece of advice. He used the method well since he could speak Arabic very well and he also memorized the Quran. In addition, he used the Al-Hikmah. The method contained logical statement, factual statements, strong arguments and absolute truth. The strategies used to convey the messages, in general, was rational and emotional. The appeals conveyed by the preacher touched the listeners or viewers. He used simple words that were easily understood by the listeners or viewers. UAH’s preaching of Islam rhetoric structure used functioned as interactive multimedia teaching materials by designing learning concept maps and compiling lesson plans using the question and answer method, modelling, and exercises.